An evaluation of HTV-SR insulators with different creepage lengths under AC and bipolar DC in marine polluted service conditions - Elombo, Andreas Iyambo (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012.